The Drosophila ecdysone receptor (EcR) gene is required maternally for normal oogenesis. - Carney, G.E.; Bender, M. (Genetics, 2000)
Oogenesis in Drosophila is regulated by the steroid hormone ecdysone and the sesquiterpenoid juvenile hormone. Response to ecdysone is mediated by a heteromeric receptor composed of the EcR and USP proteins. We have identified a temperature-sensitive EcR mutation, EcR(A483T), from a previously isolated collection of EcR mutations. EcR(A483T) is predicted to affect all EcR protein products (EcR-A, EcR-B1, and EcR-B2) since it maps to a common exon encoding the ligand-binding domain. In wild-type females, we find that both EcR-A and EcR-B1 are expressed in nurse cells and follicle cells throughout oogenesis. EcR mutant females raised at permissive temperature and then shifted to restrictive temperature exhibit severe reductions in fecundity. Oogenesis in EcR mutant females is defective, and the spectrum of oogenic defects includes the presence of abnormal egg chambers and loss of vitellogenic egg stages. Our results demonstrate a requirement for EcR during female reproduction and suggest that EcR is required for normal oogenesis.